Reduced longitudinal cardiac strain in asthma patients. (3rd April 2019) - Tuleta, I.; Eckstein, N.; Aurich, F.; Nickenig, G.; Schaefer, C.; Skowasch, D.; Schueler, R.
ABSTRACT: Objective : There is limited knowledge about the potential relationship between asthma and heart function. Aim of our present study was to examine if asthma may be associated with manifest or subclinical heart dysfunction. Methods : Seventy-two allergic mild-to-moderate and severe asthma patients and 20 matched controls were enrolled in the study. Depending on the anti-asthmatic therapy, four subgroups of asthma patients were created: patients under long-acting beta2-agonists (LABA) and inhaled cortisone without oral cortisone treatment with (1a) versus without (1b) additional omalizumab therapy; patients with LABA, inhaled cortisone and omalizumab treatment with (2a) versus without (2b) oral cortisone. Standard echocardiographic parameters as well as global longitudinal left and right ventricular strains as determined by ultrasound-based speckle-tracking method were evaluated. Furthermore, NT-pro-brain natriuretic peptide (NT-pro-BNP), immunoglobulin E (IgE), C-reactive protein (CRP), and blood count were assessed in asthma and control groups. Results : There were no relevant differences in standard echocardiographic measures between both asthma groups and the control collective. Longitudinal left ventricular strain values were reduced significantly in severe and mild-to-moderate asthma groups (−12.91 ± 0.84% and −13.92 ± 1.55%, respectively), whereas longitudinal right ventricular strain values were additionally relevantly decreased in severe asthma (−10.35 ± 1.04%) compared to the control (−16.55 ± 0.49% and −18.48 ± 1.90%, respectively). Cardiac strains were similar in subgroups 1a and 1b. In contrast, patients from subgroup 2a presented reduced heart strains and decreased lung function compared to those from 2b. CRP, IgE, and eosinophils were significantly increased in asthma versus control individuals. Conclusions : Allergic asthma, especially severe asthma is associated with subclinical impaired left and right ventricular function as determined by speckle-tracking analysis.